Optimalisasi Waktu dan Biaya melalui Value Engineering Substitusi Standar Material Baja pada Proyek EPC - Alde Noverli. Y; Rachmi Yanita (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
The implementation of Engineering, Procurement, and Construction (EPC) projects often encounters logistical and supply chain challenges, particularly when design specifications strictly adhere to foreign standards not locally available. This research evaluates the application of Value Engineering (VE) to resolve material scarcity in an integrated Central Processing Facility project in East Kalimantan. The initial design mandated Chinese standard (GB) materials, causing an 8-12 week import lead time that threatened the critical path of the lump-sum contract. Through a Technical Deviation Request (TDR), the engineering team proposed substituting GB materials with equivalent Indonesian National Standards (SNI) and ASTM materials. A multi-criteria decision analysis was utilized to ensure the structural integrity, verifying the geometric validation and mechanical capacities of local H-Beams and high-strength rebars. The results demonstrate a significant project acceleration of 30 days and a direct cost efficiency of 13% (Rp 1.625 billion). The substitution also reinforced local industry empowerment (TKDN) and minimized the carbon footprint of international logistics, all while strictly adhering to occupational health and safety (HSE) protocols.